Nitrogen use efficiency and genotype-by-environment interaction in durum wheat genotypes under varying nitrogen supply - Tesfaye Geleta Aga; Fetien Abay Abera; Tufa, Tesfaye Balemi; Abebe, Kebebew Assefa; Abeyo Bekele Geleta; Ayana, Negash Geleta (Informa UK Limited, 2024)
Nitrogen (N) use efficiency is important for wheat grain yield and quality. This study evaluated6 durum wheat genotypes in Ethiopia to determine the extent of nitrogen use efficiency (NUE) components and genotype-by-environment interactions under high and low N supply. The results showed that there was significant variation among the genotypes in grain yield and NUE components. Grain yield ranged from 3.30 to 6.22 t ha−1 under high N and 2.30 to 3.78 t ha−1 under low N conditions with an average reduction of 40.1%. Nitrogen harvest index, Nitrogen uptake efficiency (NUpE), Nitrogen utilization efficiency (NUtE) and NUE increased under low N compared to high N. NUtE varied from 28.6 to 43.9 kg kg−1 under high N and 39.5 to 51.2 kg kg−1 under low N while NUE increased from 26.4 under high N to 31.8 kg kg−1 under low N. Grain yield showed significant and positive associations with most of NUE components under both N conditions. NUpE and NUtE are the two important traits that contribute to NUE. N-efficient genotypes were found to be the most stable genotypes. Thus, the study emphasizes the importance of selecting genotypes with improved grain yield and NUE traits under low N conditions.